Meningiomas. - McDermott, Michael W. (Handbook of clinical neurology, 2020)
"Meningiomas, Volume 170, Part Two, discusses tumors that arise from the coverings of the brain and spinal cord. In this updated volume of the Handbook of Clinical Neurology, experts in the field - from basic scientists to skilled neurosurgeons, provide up-to-date synopses of each topic as it relates directly to this class of tumor. Surgical and radiation therapy, which remain the mainstays of treatment, are a major focus, but coverage also includes potential molecular avenues for the development of effective medical treatments. This book serves as a comprehensive review of the neurosurgical issues surrounding this extremely common brain tumor. Few procedures in surgery are more immediately formidable than an attack upon a large tumor of this type, hence the greatest challenge of treatment is the need to complete tumor removal without creating new neurologic deficit"--Publisher's description